FORMATION OF THE INDIVIDUAL STYLE OF FUTURE TRANSLATORS’ PROFESSIONAL ACTIVITIES: INTERNATIONAL CONTEXT - Oleh A. Lavnikov (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article analyzes the international experience of forming an individual style of professional activity of future translators. The emphasis is placed on the importance of training competitive translators with a high level of desire for personal development, knowledge of business ethics, understanding of the requirements for appearance that corresponds to the situation in professional activities, etc. The purpose of this article is a theoretical study of the process of forming an individual style of professional activities of future translators abroad for the prospect of further use of positive experience to improve the system of higher translation education in Ukraine. The experience of countries with high results in the field of training competitive personnel, namely countries with a highly developed system of training, including philological profile, is revealed. It has been established that the formation of an individual style of professional activities of future translators in Spain must take into account the market requirements, which are reflected in educational practice. The strength of the UK in this process is the introduction of independent educational courses that form such competencies as the ability to use information and communication technologies on a theoretical, practical and creative levels in professional translation activities; understand and use techniques of business communication in a particular situation, the ability to negotiate and ways to influence the interlocutor; analyze and be able to apply in professional activities the knowledge of historical aspects of translation development, etc. As a result of the analysis of foreign scientific literature, the following organizational and pedagogical conditions of formation of individual style of professional activities of future translators abroad are substantiated: taking into account the requirements and features of the market of translation services for preparation of future translators; ensuring the relationship between the educational process and real professional activity; the study of different word-forming models in a foreign language; the introduction of educational courses (technical written text, copywriting or legal editing, etc.), which are aimed at developing writing skills, etc. An important aspect of the article is discussing the process of forming the professional image of a future translator, as a component of the individual style of professional activities. It is noted that in the foreign scientific literature a lot of attention is paid to such a phenomenon as the “individual image of the translator”and the process of its formation. The main thing in the context of this problem is the creation of academic disciplines that reveal the basics of psychology of communication, imageology, psychology of interpersonal cognition.